Synthesis of pyrazine via chemoselective reduction of beta-keto-alpha-oximino ester using baker's yeast - Mo, Kilwoong; Park, Jin Hyeong; Kang, Soon Bang; Kim, Youseung; Lee, Yong Sup; Lee, Jae Wook; Keum, Gyochang (ELSEVIER, 2016)
The synthesis of pyrazines by the baker's yeast-mediated reaction of beta-keto-alpha-oximino esters and amides is described. Baker's yeast reduced oximes selectively over ketones of beta-keto-alpha-oximino esters to give the corresponding beta-keto-alpha-amino ester intermediates, which underwent spontaneous dimerization followed by air-induced aromatization to yield pyrazines. The chemoselective reduction of beta-keto-alpha-oximino amides using baker's yeast also afforded the corresponding pyrazines. Interestingly, both hydroximes and alkoximes gave the pyrazines by the baker's yeast-mediated reduction via the corresponding amino ketones, the known precursors of pyrazines. The reaction was strongly dependent upon pH of reaction medium, and gave optimum yields at pH 5. These results demonstrate that pyrazines were synthesized efficiently and eco-friendly using a whole-cell biocatalytic system as an alternative to chemical reduction. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: DYNAMIC KINETIC RESOLUTION; ENANTIOSELECTIVE SYNTHESIS; ASYMMETRIC REDUCTION; DERIVATIVES; CEPHALOSTATINS; BIOREDUCTION; LIGUSTRAZINE; CHEMISTRY; RECEPTOR; ANALOGS